Cognitive task analysis in task-based syllabus design for the teaching and learning of Kiswahili as a second language in Ugandan secondary schools - Jjingo, Caesar (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.